2010
DOI: 10.1016/j.ijid.2009.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin versus tetracycline antibiotics for the treatment of scrub typhus

Abstract: Levofloxacin is effective in patients with scrub typhus, but has a longer time to defervescence compared with tetracycline antibiotics. When levofloxacin is used for severe scrub typhus, higher mortality may be attributed to the longer time to defervescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 26 publications
(32 reference statements)
1
23
0
Order By: Relevance
“…Scrub typhus has also been transmitted by needle stick from a patient who received pefloxacin [21]. Finally, Tsai et al [10] have shown recently in a retrospective case series of 132 patients with scrub typhus that although treatment with levofloxacin was effective in 71 patients, the patients had a significantly longer time to defervescence compared with 61 patients treated with M a n u s c r i p t 10 tetracyclines. Moreover, for patients with severe scrub typhus, higher mortality was observed in the levofloxacin-treated group [10].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scrub typhus has also been transmitted by needle stick from a patient who received pefloxacin [21]. Finally, Tsai et al [10] have shown recently in a retrospective case series of 132 patients with scrub typhus that although treatment with levofloxacin was effective in 71 patients, the patients had a significantly longer time to defervescence compared with 61 patients treated with M a n u s c r i p t 10 tetracyclines. Moreover, for patients with severe scrub typhus, higher mortality was observed in the levofloxacin-treated group [10].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Tsai et al [10] have shown recently in a retrospective case series of 132 patients with scrub typhus that although treatment with levofloxacin was effective in 71 patients, the patients had a significantly longer time to defervescence compared with 61 patients treated with M a n u s c r i p t 10 tetracyclines. Moreover, for patients with severe scrub typhus, higher mortality was observed in the levofloxacin-treated group [10]. There are three reports of apparent successful scrub typhus therapy with fluoroquinolones [5,6,22], although the evidence for scrub typhus as the aetiology of the disease is uncertain for one patient [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there are no data on the efficacy of azithromycin for the treatment of complicated scrub typhus. A recent retrospective study showed that levofloxacin therapy is associated with mortality in severe scrub typhus, despite a favorable success rate in mild to moderate cases, suggesting that the treatment outcomes of antibiotics can be different for severe scrub typhus (10). In this study, we showed that the efficacy of azithromycin is comparable to that of doxycycline in complicated scrub typhus, suggesting that azithromycin can also be used as a primary agent for the treatment of severe scrub typhus infection.…”
Section: Discussionmentioning
confidence: 55%
“…For this reason, azithromycin is considered an appropriate alternative for mild to moderate scrub typhus in areas where doxycycline-resistant scrub typhus is prevalent (8), and also for children under 8 years of age or in women during pregnancy (9), where doxycycline is contraindicated. However, there are few clinical data on the efficacy of different antibiotics for the treatment of severe, life-threatening scrub typhus (10), despite the fact that complicated cases of scrub typhus are not uncommon (11)(12)(13). Moreover, the efficacy of azithromycin for the treatment of severe complicated scrub typhus is largely unknown, because all randomized clinical trials using macrolides to date have excluded severe or complicated cases (5)(6)(7).…”
mentioning
confidence: 99%